PENERAPAN MODEL MAKE A MATCH PADA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V MIN 17 PIDIE - Junaidah; Ismi Hanum (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2019)
The aim of the research is to identify whether by using the make a match type model can increase the students learning outcomes. This Classroom Action Research consists of three cycles with some stages i.e. planning, acting, observing and reflecting. The subject of the research was the 5th grade students who totally 34 students, in which consisted of 22 females and 12 males. The result of the research indicated that the students obtained the average and classical achievements respectively at cycle I was 65 and 41.18%. Cycle II was 75.29 and 70.58%. And cycle III was 92.35 and 100%. So, the finding shows if by using the model it can increase the students’ learning outcomes.